The Association of General and Central Obesity with Dietary Patterns and Socioeconomic Status in Adult Women in Botswana - Boitumelo Motswagole; Jose Jackson; Rosemary Kobue-Lekalake; Segametsi Maruapula; Tiyapo Mongwaketse; Lemogang Kwape; Tinku Thomas; Sumathi Swaminathan; Anura V. Kurpad; Maria Jackson (Journal of Obesity)
Dietary patterns and their association with general and central obesity among adult women were studied using a cross-sectional survey with multistage cluster sampling in urban and rural areas nationwide in Botswana. The participants in the study were adult women (N = 1019), 18–75 years old. The dietary patterns were identified using principal component analysis, and their associations with the body mass index and the weight-for-height ratio were examined. Factor analysis with varimax rotation was used to identify six dietary patterns (fast foods, refined carbohydrates, vegetables and fruits, fish and nuts, Botswana traditional foods, and organ and red meat dietary pattern). Overall, 24.5% of the women were overweight (BMI 25.0–29.99 kg/m2) and 24.5% were obese (BMI > 30 kg/m2). A waist-to-height ratio greater than 0.5 was observed for 42.2% of the women. With adjustment for age and education, individuals in the highest tertile of the Botswana traditional food pattern had a significantly higher risk of general obesity (RR = 1.40, 95% CI: 1.07–1.84) and central obesity (RR = 1.20, 95% CI: 0.97–1.48). With respect to the fish and nut pattern, a significant association was observed with central obesity only (RR = 1.43, 95% CI: 1.18–1.72). The Botswana traditional food pattern, characterised by a high carbohydrate intake, was found to be associated with a high risk of obesity in this study. However, more research is required to assess other factors contributing to obesity in women so that appropriate intervention programs can be put in place to help control this epidemic.